The Urgence of Values in Islamic Education (Syed Muhammad Naquib al-Attas Thought Study) - Arif Rahmatullah; Syamsul Hidayat; Muh. Nur Rochim Maksum (TSAQAFAH, 2022)
human life, including in the world of education. However, behind the rapid development that has occurred, it turns out that there is also a severe problem, namely the crisis of values which includes morals, manners, and human spirituality. The emergence and development of these problems stem from a secular worldview, where God and religion are not central and influential in life activities. This has resulted in the deconsecration of values, which in the end everything that is done in life is only materialistic. Even in the education sector, it is more directed to produce pragmatic education so the education mostly only prioritizes job skills without paying attention to the morality of educational output. Therefore, many people have the skills to work, but in terms of morals, etiquette, and spirituality, they are left behind. This differs diametrically from the Islamic worldview which makes God the primary goal of life. Thus, Islam does not experience problems regarding the relationship of religion and life. Islam views on education is not only to fulfill worldly needs but also more than that, education is something that people needs to make themselves the best human being (Insan Kamil). Education in Islam also serves to get closer to Allah SWT, with the increase of knowledge that people gain through education, the quality of their worship of Allah SWT will also increase. Therefore, the worldview of values in education will determine how the process and the output of education itself. Assuming that the worldview has been embedded in educators and students. Then, the value of education will be the value of quality, because the educational process carried out of aims to produce quality outputs and outcomes. This is the reason why S.M.N al-Attas uses the concept of Ta’dib orders to instill the values that need to be built in Islamic education. Hence, this article is expected to provide the following implications: First, the shift in the worldview of educators and students; Second, provide orientation to the process of Islamic education; Third, encourage improvements and refinements to the process of Islamic education.